2022
DOI: 10.1111/eci.13894
|View full text |Cite
|
Sign up to set email alerts
|

A Mendelian randomization study on causal effects of leisure sedentary behaviour on the risk of rheumatoid arthritis

Abstract: Background The causal inference between leisure sedentary behaviour (LSB) and rheumatoid arthritis (RA) is still controversial because of potential residual confounding and reverse causality. Methods The present study used publicly available large‐scale genome‐wide association studies (GWAS) of LSB (television watching, computer use, and driving) and RA to perform a two‐sample Mendelian randomization (MR) study to evaluate the causal effect of LSB on the risk of RA. We detected significant causal associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Leisure sedentary behavior is any waking behavior with an energy expenditure less than 1.5 metabolic equivalents in a sitting, reclining, or lying posture, including sedentary television watching, computer use, and driving, excluding sitting at work ( 36 ). The main cause of vascular endothelial dysfunction due to sedentary sitting is the reduction in muscle activity and the subsequent reduction in energy demand leading to a decrease in peripheral blood flow, causing a decrease in shear stress, which in turn increases vasoconstriction, leading to vascular dysfunction ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leisure sedentary behavior is any waking behavior with an energy expenditure less than 1.5 metabolic equivalents in a sitting, reclining, or lying posture, including sedentary television watching, computer use, and driving, excluding sitting at work ( 36 ). The main cause of vascular endothelial dysfunction due to sedentary sitting is the reduction in muscle activity and the subsequent reduction in energy demand leading to a decrease in peripheral blood flow, causing a decrease in shear stress, which in turn increases vasoconstriction, leading to vascular dysfunction ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies ( 7 , 8 ) have shown the protective effect of physical activity in OA, other studies revealed the negative effects of exercise in promoting the development of OA. Sedentary behavior includes sedentary computer use, watching television, and driving ( 9 ). An increase in leisure and sedentary behavior is associated with a higher risk of mental illness ( 10 ) and cancer ( 11 ).…”
Section: Introductionmentioning
confidence: 99%